UPAYA MEMPERTAHANKAN DISIPLIN KERJA STAF BAGIAN KEUANGAN KODAM VI/MULAWARMAN BALIKPAPAN KALIMANTAN TIMUR (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The general aim of this research is to find out why the work discipline of the Finance Section staff of Kodam VI/Mulawarman Balikpapan is still not optimal, to formulate efforts to improve the work discipline of the staff of the Finance Section of Kodam VI/Mulawarman Balikpapan East Kalimantan.The results of the research found that the work discipline of the Finance Section staff of Kodam VI/Mulawarman Balikpapan was still not optimal because not all staff had awareness of work discipline, and there was still a small portion of the Finance Section staff who were not ready to accept and carry out superiors' orders, not all of the Finance Section staff of the Kodam VI/Mulawarman Balikpapan in the first semester of 2023 has compliance with work discipline so compliance still needs to be improved because there are still members who are absent from religious activities, morning assembly activities, mental education activities and others for various reasons, not carrying out their duties in the financial sector in accordance with SOPs, lack of competence in the financial sector and not all staff adhere to work discipline, so it is still not optimal because there are still members who lack consistency and commitment in carrying out their duties in the Finance Department. Efforts to increase the work discipline of the staff of the Finance Section of Kodam VI/Mulawarman Balikpapan by (1) efforts to increase awareness. The work discipline of the staff of the Finance Section of Kodam VI/Mulawarman Balikpapan is directed at strengthening morality, solidarity, national insight and love of the homeland through example, loyalty based on the Sapta Marga, Soldier's Oath and the Eight Obligations of the TNI, (2) Increased compliance by motivating personnel from the realization of personnel mental development programs such as religious activities, (3) Increased Obedience with every military personnel in the Finance Section of Kodam VI/Mulawarman Balikpapan when carrying out their official duties, they are required to memorizing the Sapta Marga, the Oath of the Eight Military Compulsory Soldiers as the beginning of an effort to increase military personnel's understanding of discipline and order as well as individuals so as to increase awareness and obey the law, including human rights, for personnel.
Keywords: Work Discipline